1992
DOI: 10.1002/syn.890110404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐dose methamphetamine on monoamine uptake sites in rat brain measured by quantitative autoradiography

Abstract: The neurotoxicity of methamphetamine to monoaminergic neurons was examined. Neurotoxicity was assessed by quantitative autoradiography using radioligands specific for binding to norepinephrine, dopamine, and serotonin uptake sites. High-dose administration of methamphetamine led to decreases in binding to uptake sites for the three monoamines. Norepinephrine binding sites were decreased in certain amygdaloid nuclei and in the dorsomedial hypothalamic nucleus. Serotonin binding sites were reduced in widespread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…As shown in Tables 3 and 4, K + -depolarization in neostriatum produced a significant increase of striatal, but also of nigral Dyn B levels, indicating a monosynaptic interaction. While the effect of high doses of Meth on DA release has been extensively demonstrated (O'Dell et al 1991;Kuczenski and Segal 1992;Nash and Yamamoto 1992;Abekawa et al 1994), this is the first time that the effect of Meth on monoamines, amino acids and neuropeptides is simultaneously analysed in substantia nigra and neostriatum, which is relevant, as the neurotoxic effect of Meth has been observed in terminals, but not in cell body regions (Brunswick et al 1992).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As shown in Tables 3 and 4, K + -depolarization in neostriatum produced a significant increase of striatal, but also of nigral Dyn B levels, indicating a monosynaptic interaction. While the effect of high doses of Meth on DA release has been extensively demonstrated (O'Dell et al 1991;Kuczenski and Segal 1992;Nash and Yamamoto 1992;Abekawa et al 1994), this is the first time that the effect of Meth on monoamines, amino acids and neuropeptides is simultaneously analysed in substantia nigra and neostriatum, which is relevant, as the neurotoxic effect of Meth has been observed in terminals, but not in cell body regions (Brunswick et al 1992).…”
Section: Discussionmentioning
confidence: 94%
“…The long-term effects of Meth are largely restricted to the nigrostriatal DA system (Ricaurte et al 1980;Marshall and Navarrete 1990;Marshall et al 1993;Burrows and Meshul 1997). Short-and long-term effects have also been described in limbic and cortical systems, but these systems are less and differently affected than the neostriatum (Axt and Molliver 1991;Brunswick et al 1992;Eisch et al 1996). Furthermore, while, as measured by quantitative autoradiography, the neurotoxic effect of Meth is seen in widespread brain regions receiving monoamine terminals, the cell body regions are largely unaffected (Brunswick et al 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the hippocampus also is innervated by the dorsal raphe efferents. Brunswick et al (1992) had demonstrated that high-dose MAP can decrease serotonin uptake site in this region. Sharkey et al (1991) examined the effects of repeated methylenedioxymethamphetamine (MDMA 20 mg/kg, s.c., twice daily for 4 days, 14 days later) upon hippocampal function by using the [14C]-2DG and [3H] paroxetine 5-HT binding site autoradiographic methods and found that profound losses of [3H] paroxetine labelled uptake sites accompanied by significant increases in LCGU in the hippocampal fields CA2, CA3 and dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that serotonergic raphe bodies appear to be resistant to the neurotoxic effects of a number of neurotoxic amphetamine-like compounds (Brunswick et al 1992) The discrepancy may be due to the study method because the 2DG method detects the change in the synaptic activity rather than the neuron body.…”
Section: Discussionmentioning
confidence: 99%